Long-term outcomes of systemic corticosteroid-sparing immunomodulatory therapy for Birdshot Retinochoroidopathy. (17th August 2020) - You, Caiyun; Lasave, Andres F.; Kubaisi, Buraa; Syeda, Sarah; Ma, Lina; Wai, Kelvin Cheng Kah; Diaz, Mikhail Hernandez; Walsh, Marisa; Stephenson, Andrew; Montieth, Alyssa; Foster, C. Stephen
ABSTRACT: Purpose: To report the visual prognosis, electroretinography (ERG) and perimetry outcomes of systemic corticosteroid-sparing immunomodulatory treatment (IMT) for birdshot retinochoroidopathy (BSRC). Methods: Retrospective non-comparative case series of 132 patients (264 eyes) with BSRC treated with IMT from Massachusetts Eye Research and Surgery Institution. Results: The average follow-up time was 60.1 months. After one year on IMT, 39.4% showed no clinically active inflammation. After 5 years of IMT, 78.0% had no signs of clinical inflammation. No significant differences were observed on best-corrected visual acuity (BCVA), ERG parameters, and perimetry parameters between baseline and subsequent visits on IMT. Conclusion: Long-term systemic corticosteroid-sparing IMT was associated with a low rate of BSRC disease exacerbation. While differences were seen on testing parameters, they were not consistent trends and difference were attributed to variability of testing or fluctuation of inflammation that may be expected in the course of the disease.